The role of Social Workers in Achieving Social Welfare in Social institutions at Qalqilya Governorate from the Perspective of the community’s Organization - Abu Elbah, Mohammed Bassam (Journal of Humanities & Social Sciences, 2022)
The study aimed to identify the extent to which the social welfare policy is achieved in the social institutions in Qalqilya governorate from the perspective of the method of community organization, and also aimed to identify the presence of statistically significant differences due to the variables (gender, place of residence, educational qualification, years of experience), the researcher used the descriptive approach in The study population consisted of social workers in Qalqilya Governorate. The sample size was (50) male and female specialists, who were randomly tested and entered into the computer and statistically processed using the statistical program for the social sciences (SPSS) where arithmetic averages, percentages, and one-way ANOVA were used. T also, where the research questionnaire included (30) items. Study results, study sample responses on all axes, arithmetic averages and ratios, percentage, assessed high, percentage (78.72%). The statistics also indicate that there is no sign indicating the existence of statistical studies at the level of significance about the specialist in making social policy in the Palestinian society from the perspective of the method of organization attributed to the community (place of residence, educational qualification, years of experience), but it was found on the variable (gender) in favor of meals. 1.Activating the participation of social planners when setting policies for his contribution to defining clear elements of social welfare policies. 2.To contact members of the community to identify their unsatisfied needs, problems and unavailable community resources.